Dental fragment embedded in the lower lip after facial trauma: Brief review literature and report of a case - Dorina Lauritano; Massimo Petruzzi; Gerardo Sacco; Guglielmo Campus; Francesco Carinci; Lucio Milillo (Wolters Kluwer Medknow Publications, 2012)
Upper incisors are the most frequently involved teeth in traumatic dental injuries. Soft tissues (lips and/or oral mucosa) adjacent to incisal edge can receive direct and/or indirect traumas. Laceration of the lower lip is a not rare eventuality and teeth fragments could be embedded in labial soft tissue. The reattachment of these fragments, if possible, is the elective treatment choice, thanks to the modern adhesive and restorative techniques. The authors present a case of a white Caucasian 10-year-old child, who attended the dental clinic for the treatment of both upper central incisors' crown fractures. The fragment of the left incisor was retrieved embedded in the lower lip. It was successfully surgically removed and reattached using a composite adhesive technique. A careful clinical and radiographic examination with the surgical removal of tooth fragments could prevent undesirable foreign body reaction, infection and scarring. The authors also reviewed the most relevant literature concerning tooth fragment reattachment after removal from oral soft tissues.